Deltoid ligament injury and repair - Loek Loozen; Andrea Veljkovic; Alastair Younger (Journal of Orthopaedic Surgery, 2023)
The deltoid ligament is the primary stabilizer of the medial side of the ankle joint. It is a complex structure with an origin at the medial malleolus from where it spreads fan shaped distally with an insertion into the medial side of the talus, calcaneus and navicular bone. This chapter gives an overview of the anatomy, function, and pathology of the deltoid ligament. The deltoid ligament can become insufficient as a result of an ankle injury or prolonged strain. In the acute setting, deltoid insufficiency often coincides with multi ligament injury the ankle joint; syndesmosis injury, or ankle fractures. Management in the acute phase remains a subject of debate. Some orthopedic surgeons have a tendency towards repair, whereas most trauma surgeons often treat the deltoid nonoperatively. In the chronic setting the ligament complex is often elongated as a result of prolonged strain. It often coexists with a hindfoot valgus, as is the case in planovalgus feet. In such a case a realignment procedure should be combined with the deltoid repair.